Comparison of prenatal anti‐D titration testing by gel and tube methods: A review of the literature. Issue 6 (2nd April 2021) - Lieberman, Lani; Andrews, Jennifer; Evans, Michael D.; Cohn, Claudia S.
Abstract: Background: Antenatal titration testing is traditionally performed using a manual tube test. Tube testing has limitations; it is a manual, time‐consuming method with wide interobserver variability. Gel‐based testing is an attractive alternative because it is more precise and can be automated. This study's objective was to summarize the published literature that assessed the relationship between titrations performed by tube and gel for anti‐D alloimmunized pregnancies. Study Design and Methods: A comprehensive literature search was performed. Articles were selected if research was original and compared at least five pairs of anti‐D titration tests performed by gel and tube. Differences in the number of dilutions between gel and tube methods were compared overall by study and cell type using linear models. Results: A total of 512 articles were identified; eight were included, and titer data from 384 tube and gel pairs were abstracted. The median anti‐D titer in tube was 8 (range 0–2048) and by gel was 64 (range 0–4096). Anti‐D gel titration results were 2.1 (95% CI; 1–3.3) additional dilutions greater than in tube. Most studies utilized double‐dose reagent cells for testing. At a tube titer of 16, the sensitivity and specificity of gel titrations is maximal (91% and 94% respectively) at a gel titer of 64. Conclusion: Overall, titrations performed by gel were two dilutions higher than the corresponding tube titer. For titrations, double‐dose reagent cells should be considered to standardize practice. A rigorous prospective study is needed to compare tube titrations with gel titrations using a standardized process.